2001
DOI: 10.1542/peds.107.2.e17
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Vaccine Risk/Benefit Communication in Private Practice Office Settings: A National Survey

Abstract: ABSTRACT. Communication about childhood vaccine risks and benefits has been legally required in pediatric health care for over a decade. However, little is known about the actual practice of vaccine risk/benefit communication.Objectives. This study was conducted to identify current practices of childhood vaccine risk/benefit communication in private physician office settings nationally. Specifically, we wanted to determine what written materials were given, by whom, and when; what information providers thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 17 publications
5
85
0
2
Order By: Relevance
“…Rather, they preferred short handouts, checklists, review articles, and notices or monthly medical newsletters from their professional organizations that provide to-SUPPLEMENT S333 by guest on May 9, 2018 http://pediatrics.aappublications.org/ Downloaded from the-point information to help them educate parents more effectively. This is consistent with previous studies about communicating with parents regarding childhood immunizations, [10][11][12][13] in which physicians indicated that they wanted only a brief checklist of information that would prepare them to educate parents effectively. The to-the-point information providers requested included a list with definitions of the diseases for which testing can be performed, the specific diseases for which testing is performed in their state, and sources of additional information.…”
Section: Summary Of Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Rather, they preferred short handouts, checklists, review articles, and notices or monthly medical newsletters from their professional organizations that provide to-SUPPLEMENT S333 by guest on May 9, 2018 http://pediatrics.aappublications.org/ Downloaded from the-point information to help them educate parents more effectively. This is consistent with previous studies about communicating with parents regarding childhood immunizations, [10][11][12][13] in which physicians indicated that they wanted only a brief checklist of information that would prepare them to educate parents effectively. The to-the-point information providers requested included a list with definitions of the diseases for which testing can be performed, the specific diseases for which testing is performed in their state, and sources of additional information.…”
Section: Summary Of Findingssupporting
confidence: 90%
“…[8][9][10][11][12][13] After examining current pertinent literature, 1-3,14-23 the team drafted a focus group moderator's guide with scripted questions.…”
Section: Development Of Moderator's Guidementioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] After examining current pertinent literature, 14 Parents were also asked what information they wanted and how they wanted it delivered (eg, when, in what format, and by whom). Parents were shown newborn hearing screening brochures developed previously by various states and were asked to give specific feedback on the content, wording, graphics, layout, and organization.…”
Section: Development Of Moderator's Guidementioning
confidence: 99%
“…As a possible consequence of these trends, recent national surveys found that 23% of parents questioned the number of shots recommended for their children, 1 and 25% were concerned that vaccines might weaken the immune system. 1 Because most parents receive information and recommendations about vaccines from their doctors, 2 and because these recommendations carry substantial weight with parents, 3,4 providers must be knowledgeable when addressing parents' concerns. This article will provide health care professionals with information about the effect of vaccines on the infant's immune system and the capacity of the immune system to respond safely to multiple vaccines.…”
mentioning
confidence: 99%